Acetylcholinesterase Inhibitory Activity and Antioxidant Activity of Selected Medicinal Plant Extracts Used Against Cognitive Dysfunction and Memory Loss in Sri Lankan Traditional Medicine - Attanayake, Anoja Priyadarshani; Jayatilaka, Kamani Ayoma Perera Wijewardana (Asian Journal of Pharmaceutical Research and Development, 2018)
The objectives of the study were to determine the acetylcholinesterase (AChE) inhibitory activity and antioxidant activity in the selected Sri Lankan medicinal plants. AChE inhibitory activity of the selected medicinal plant extracts was determined using the Ellman’s method. The antioxidant activities were determined by four in vitro methods namely DPPH assay, FRAP assay, NO assay and TBA acid method. The contents of total polyphenols and flavonoids were determined quantitatively.Out of the ten selected medicinal plant extracts Abrus precatorius, Centella asiatica, Strychnos nux-vomica and Ricinus communis showed IC50 values < 200 µg/mL for AChE inhibitory activity. A high antioxidant activity was shown in the extracts of Cardiosprmum halicacabum, Centella asiatica and Ricinus communis in the four selected antioxidant assays. The total polyphenol content and total flavonoid content was in the range of 0.55-7.30 mg/g DW and 19.08±0.29-1283.08± 0.09 µg/gDW. The extracts of A. precatorius, C. asiatica, S. nux-vomica and R. communis are deserved to be as potent sources of AChE inhibitors as well as natural antioxidants. Considering the complex multifactorial etiology of Alzheimer’s diseases, these plant extracts would be apt candidates for the development of novel pharmaceutical agents in the management of Alzheimer’s diseases.